Association of Hospitalised Infection With Socioeconomic Status in Patients With Rheumatoid Arthritis Receiving Biologics or Tofacitinib: A Population-Based Cohort Study - Hsin-Hua Chen; Hsin-Hua Chen; Hsin-Hua Chen; Hsin-Hua Chen; Hsin-Hua Chen; Hsin-Hua Chen; Hsin-Hua Chen; Ching-Heng Lin; Ching-Heng Lin; Ching-Heng Lin; Ching-Heng Lin; Ching-Heng Lin; et al. (Frontiers in Medicine, 2021)
Objectives: Use of biologics or targeted synthetic disease-modifying anti-rheumatic drugs (b/tsDMARDs) is associated with infection in patients with rheumatoid arthritis (RA). Socioeconomic status is substantial in infectious diseases; however, the impact of socioeconomic status on risk for infection in patients with RA receiving b/tsDMARD remains unclear.Methods: We used the 2003–2017 Taiwanese National Health Insurance Research Database to identify patients with RA receiving b/tsDMARDs. A Cox regression analysis was used to estimate the associations of covariates with the risk of hospitalised infection shown as hazard ratios (HRs) with 95% confidence interval (CIs).Results: We identified 7,647 RA patients who started their first bDMARD/tsDMARD treatment. Log-rank analyses demonstrated the association between age (p < 0.001), urbanisation (p = 0.001), the insured amount (p = 0.021), and the hospitalisation. Cox proportional regression analyses showed that age was independently associated with hospitalised infection in a dose–response manner, whereas a high-income category had an inverse association (HR 0.48, 95% CI 0.23–0.96). Hospitalisation for infection within 5 years was a strong risk factor (HR 5.63, 95% CI 1.91–16.62), and living in a rural area tended to be a risk factor (HR 1.76, 95% CI 0.98–3.14) for incident hospitalised infection.Conclusions: This study showed the crucial impacts of age, socioeconomic status, and history of infection on hospitalised infection in patients with RA receiving b/tsDMARDs. These findings highlight the largely ignored role of socioeconomic status in risk stratification among patients receiving b/tsDMARDs for RA.